International survey of research university faculty : use of altmetrics. (Primary Research Group, 2017)
"The report is based on data from 325 faculty at major research universities in the USA, Canada, the UK, Ireland and Australia, about their use of altmetric measures such as altmetric badges, Altmetrics.com, Plum Analytics and social media measures. The study presents detailed data on the percentage of scholars who track use of or citiations of their works on LinkedIn, Facebook, YouTube, OpenSyllabus, research aggregation platforms, Mendeley and many other venues." -- Publisher's website.